LINGUO-PRAGMATIC FEATURES OF TRANSLATING INTERNATIONAL ECONOMIC CORRESPONDENCE (KONFERENSIYA, 2025)
This article explores the linguo-pragmatic features of translating internationaleconomic correspondence and identifies key factors influencing the adequacy andequivalence of translation in the economic domain. Economic correspondence, as aspecialized form of written business communication, requires a high degree ofterminological precision, pragmatic awareness, and intercultural competence. Thestudy highlights typical translation challenges related to lexical non-equivalence,pragmatic misinterpretation, genre specificity, and structural complexity of economictexts. Special emphasis is placed on the translator’s background knowledge,communicative intent analysis, and the ability to interpret legal, financial, andcommercial terminology accurately. The findings demonstrate that economictranslation is inherently interdisciplinary and demands strong linguistic, cognitive,and analytical skills to ensure accurate intercultural communication